2014
DOI: 10.1016/j.redox.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase-3 mediates TNF-stimulated oxidant activity in skeletal muscle

Abstract: AimsSphingolipid and oxidant signaling affect glucose uptake, atrophy, and force production of skeletal muscle similarly and both are stimulated by tumor necrosis factor (TNF), suggesting a connection between systems. Sphingolipid signaling is initiated by neutral sphingomyelinase (nSMase), a family of agonist-activated effector enzymes. Northern blot analyses suggest that nSMase3 may be a striated muscle-specific nSMase. The present study tested the hypothesis that nSMase3 protein is expressed in skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…A recent report showed that this enzyme could play a role in DNA damage responses in human tumorigenesis (Corcoran et al, 2008) and in response of oxidative stress in skeletal muscle (Moylan et al, 2014). Clearly additional studies are needed to address the role of nSMase3 in cancer and in sphingolipid biology.…”
Section: Nsmase In Pathophysiologymentioning
confidence: 99%
“…A recent report showed that this enzyme could play a role in DNA damage responses in human tumorigenesis (Corcoran et al, 2008) and in response of oxidative stress in skeletal muscle (Moylan et al, 2014). Clearly additional studies are needed to address the role of nSMase3 in cancer and in sphingolipid biology.…”
Section: Nsmase In Pathophysiologymentioning
confidence: 99%
“…32 Similar to our findings, TNF-α is increased in patients with HFrEF [33][34][35] and is a key factor regulating muscle mass, 36 which can activate the expression of atrogenes such as MuRF1 and MafBx 37 while suppressing anabolic factors such as IGF-1, 38 while also further mediating oxidative stress. 39 In addition, TNF-α can downregulate PGC-1α expression and thus impair mitochondrial function. 40 That we too found such alterations in our HFrEF animals simultaneous with increased plasma TNF-α levels strongly suggests a causal role of this cytokine in mediating skeletal muscle alterations between HF cohorts-a suggestion further supported by our HFpEF animals having unchanged plasma concentrations of TNF-α alongside fewer skeletal muscle alterations.…”
Section: Underlying Mechanisms Of Divergent Skeletal Muscle Alteratiomentioning
confidence: 99%
“…Although nSMase-3 (from now on indicated as SMPD4), encoded by SMPD4, has no significant sequence homology with other sphingomyelinases, some papers reported its catalytic activity and described regulation of its expression by tumor necrosis factor and p53, implicating this protein in response to cellular stress. [4][5][6] SMPD4 is a 866 amino acid long protein with a protein-protein interaction domain and a C-terminal transmembrane domain close to the putative enzyme active site, which includes a potential N-glycosylation site. 5,6 Subcellular localization experiments have shown the presence of SMPD4 at the endoplasmic reticulum (ER) and the Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] SMPD4 is a 866 amino acid long protein with a protein-protein interaction domain and a C-terminal transmembrane domain close to the putative enzyme active site, which includes a potential N-glycosylation site. 5,6 Subcellular localization experiments have shown the presence of SMPD4 at the endoplasmic reticulum (ER) and the Golgi apparatus. In independent studies, proteomics analysis of nuclear fractions detected SMPD4 at the nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%